Factors influencing the energy intensity of automotive manufacturing plants - Dehning, Patrick; Thiede, Sebastian; Mennenga, Mark; Herrmann, Christoph (Journal of cleaner production, 2017)
Intensifying market pressure, new legislations, increasing environmental consciousness and rising energy prices are a major concern for manufacturing companies worldwide. Especially the energy demand in manufacturing and consequently the energy costs and related environmental impacts of production are in focus of decision makers. In this context, multi-national companies like automotive manufacturers are interested to know how a specific plant performs in comparison to others and which factors influence its energy performance. Against this background, this paper provides an insight how the multiple linear regression approach can be used to identify and quantify factors influencing the energy intensity of automotive plants. The presented model aims at supporting strategic decision making and forecasting of the future energy demand of an automotive plants.